(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We present the approximate solution for mathematical model for Breast Cancer (BC) over three time intervals. The suggested approach depends homotopy perturbation method developed with Chebyshev series (CHPM). Special attention to give the convergence analysis of the CHPM. The residual error function (REF) is calculated and used as a basic criterion in evaluating the efficiency/accuracy of the presented numerical scheme. We utilize the exact solution for comparison with the results of the method used. Through these results, we can confirm that the applied technique is an effective tool to give a simulation of such models. To confirm the validity and usefulness of the proposed procedure, illustrative instances are given.